The effect of usability and information quality on Malaysian user’s satisfaction of student information systems in higher education institutions - Atta, Mohammed Thamir (2019)
The vast development in information systems has changed the performance of all kinds of organizations including Higher Education Institutions (HEIs). Today, most of universities in developing countries like Malaysia have adopted Student Information System (SIS) that provides online services for students. The problem statement of this study lies in the gap of literature in enhancing quality SIS. The literature of information system, shows certain gaps in developing a quality model based on usability of SIS. In particular, further researches in SIS is required to investigate the integration of quality variable in the theory of DeLone & McLean (D&M). Thus the aim of this research is to adopt D&M theory that correlates four variables namely usability, information quality, the intention to use SIS, and user’s satisfaction in adopted usability website model. To achieve this objective, this study investigated the effect of usability and information quality of SIS on user’s satisfaction as well as validating the mediation role of intention to use SIS in this model. The main significance of this study lies in filling the gaps with regard to D&M theory and validate an update version of this model based on usability influence within the context of HEI. Moreover, a validation of success model for SIS based on D&M theory is achieved in this study. The methodology used to achieve these objectives is a quantitative approach. Data collection instrument is questionnaires which are distributed to a sample of postgraduate students in Malaysian universities. This study used purposive random sampling where the target respondents are SIS users. The result of this study showed that usability and information quality of SIS affect user’s satisfaction significantly. In addition to that, intention to use SIS plays an influential mediating role between usability and user's satisfaction. The outcome of this study will contribute to the theories of information systems in general and SIS in particular. Moreover, this the result of this study revealed that usability and information quality are empirically proven to be significant factors in implementing D&M success model in SIS domain.